Promoting Public Health Awareness Through Community Engagement Programs - Elda Fitriana; Panagis Galiatsatos (Journal of Community Action, 2026)
Public health awareness remains a central challenge in disease prevention and health promotion efforts, particularly in diverse and underserved communities. Community engagement programs have increasingly been recognized as effective strategies to bridge gaps between health systems and populations. This study aims to analyze how community engagement programs promote public health awareness by synthesizing empirical evidence from international and Indonesian contexts. The study employed a narrative literature review design, drawing on peer-reviewed journal articles, policy-oriented publications, and community-based program reports published between 2021 and 2025. Data were analyzed thematically to identify dominant engagement strategies, mechanisms of impact, and contextual factors influencing effectiveness. The results indicate that community engagement programs enhance public health awareness through participatory education, empowerment-based interventions, culturally responsive communication, and sustained partnerships. Programs that actively involve community members in decision-making processes demonstrate higher levels of knowledge retention, behavior change, and program sustainability. The findings also reveal that trust-building and local leadership play critical roles in translating awareness into preventive action. This study concludes that community engagement is not merely a supportive strategy but a core mechanism for effective public health promotion. Integrating inclusive, participatory, and context-sensitive approaches is essential to achieving equitable and sustainable health outcomes.